PENGARUH BRAND IMAGE DAN BRAND LOVE TERHADAP BRAND LOYALTY (STUDI PADA PEMILIK MEMBERSHIP CARD ORYZA GYM SEMARANG) - Cintya Agatha; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2020)
Exercise is important for everyone to ensure the fitness and healthiness of one's body. Recently, exercise can easily be done even indoors, utilizing technology-based fitness equipment. This condition encourages certain businessmen to set up fitness centers. One of the fitness centers located in Semarang City is Oryza Gym. The purpose of this research is to acknowledge the effect of brand image and brand love on brand loyalty for Oryza Gym’s membership card owners. Data acquisition is carried out using questionnaires handed out to 100 respondents, patrons of Oryza Gym Semarang with membership card. The result of the study shows the variables of brand image and brand love on brand loyalty of Oryza Gym Semarang. Correlation coefficient variables of brand image and brand love on brand loyalty show a very strong correlation, and if the brand image and brand love variables increase or decrease, it significantly affects the brand loyalty variable. Thus, based on the results then this study recommends Oryza Gym Semarang to improve both the quality and quantity of fitness equipment, improve the hospitality of the staff, and maximize the role of trainers.